Dentinal microcracks and cemental tears related to chemo‐mechanical root canal instrumentation: a micro‐CT Cadaver Study. (19th November 2021) - Tan, VL; Hardiman, R; Pilbrow, V; Parashos, P
Abstract: Background: The prevalence of radicular defects after root canal instrumentation is unresolved. This study used micro‐CT to assess the relationship between the formation of radicular defects and chemo‐mechanical instrumentation in a cadaver model. Methods: Maxillary and mandibular molars (n = 24) were sectioned from cadaver specimens as a tissue block containing the teeth, alveolar bone and attached mucogingival tissues. After a baseline micro‐CT scan (13.45 μm), the specimens were distributed into 3 groups (n = 8 molars): Reciproc ®, ProTaper Next™ and Mtwo ® . Micro‐CT scans of each specimen were obtained after access, glide path and preparation with each instrument. The pre‐operative and final post‐operative micro‐CT cross‐sectional images of the roots were screened by two blinded examiners to identify any pre‐existing and new radicular defects. Pre‐existing and new radicular defects were examined histologically. Results: Overall, 16 pre‐existing radicular defects were identified in 12 of the 24 molars (50%). Most of these were cemental tears (87.5%), and not true dentinal microcracks. New dentinal microcracks were observed in the post‐operative micro‐CT scans of only 3 canals (3.9%; 3/77). However, only one of these defects was found to be present histologically. Conclusions: Within the limitations of the study, chemo‐mechanical instrumentation did not routinely promote the formation of radicular defects.